Effect of deficit irrigation on the postharvest of pear variety Triunfo de Viena (iPyrus communis /iL.) in Sesquile (Cundinamarca, Colombia) (2017)
A technique settled to optimize the use of water resources is known as Controlled Deficient Irrigation (CDI), for which this experiment was carried out to determine the effect of a three water laminae: 100 (T1), 25 (T2) and 0% (T3) crop/s evapotranspiration (ETc) on the rapid growth phase of the pear fruit variety Triunfo de Viena.The fruit quality (fresh weight variation, osmotic potential, color, acidity, soluble solids, CO2 emission, dry matter, volume, firmness, ripeness index and moisture content) was evaluated over a two-month storage period. The first quality measurement was taken 2 days after harvest (DAH 8), with significant differences between treatments according to the Duncan test (P≤0.05):the largest fruit size was achieved with 100% ETc, (its diameter and volume were 7.70 cm nd 217.5 cm3, respectively.), the firmness was higher in the treatment without water (T3), with a value of 8.02 N; however, during the rest of the storage time, there were no significant differences, showing water restriction during the rapid growth phase of the fruit provided 100% water savings without compromising quality in terms of fresh weight, total titratable acidity, color index, total soluble solids and moisture content.